Array of 8 Circularly Polarized Microstrip Antenna for 802.11ac MIMO WLAN - Sholihin lihin hin (JAICT, 2016)
An Array of 8 Circularly Polarizer Microstrip Antenna was proposed as MIMO antenna for IEEE 802.11ac MIMO WLAN system. The proposed antenna is applied for access point side. Antenna arrangement in two different polarization has investigated and the results show that setting the adjacent element with different polarization such as right hand and left hand circular polarization was used to suppress the mutual coupling between antenna. The highest mutual coupling is -26.8 dB. Each antenna element covers 480 MHz bandwidth. The calculation of estimated MIMO capacity that supported by the antenna shows that 1 Gbps capacity can be reach using the proposed antenna.